Bioactivity of Songga Wood (Strychnos ligustrina) methanol extract: Antioxidant and Anti-inflammatory against Interleukin-8 (IL-8) levels in Vivo: Bioaktivitas ekstrak metanol Kayu Songga (Strychnos ligustrina): antioksidan dan Antiinflamasi terhadap kadar Interleukin-8 (Il-8) secara in Vivo - Jabbar, Asriullah; Wahyuni, Wahyuni; Nasrudin, Nasrudin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Background: Songga wood (Strychnos ligustrina) from the genus Loganiaceae is a plant that is empirically used as a traditional medicine by people in several regions in Indonesia. This plant serves as a medicine for fever, malaria, as an antidote, and for treating wounds, boils, acne and scabies. Objectives: This study aims to determine the antioxidant and anti-inflammatory activity of methanol extract of songga wood with Interleukin-8 (IL-8) parameter. Material and Methods: Songga wood was macerated with methanol for 3x24 hours until a thick extract was obtained. Antioxidant activity test was conducted using the DPPH method and anti-inflammatory test was performed using ELISA with IL-8 parameter. Test animals were divided into six groups:the normal group, negative control (Na-CMC), positive control (diclofenac sodium) and treatment with three dose variations, 50, 100, and 200 mg/kgBB. Results: The results showed that the antioxidant activity value of Songga wood was IC50 84.51 µg/ml. Furthermore, anti-inflammatory activity showed IL-8 levels at doses of 50 mg/kgBB extract (494.8 pg/ml), 100 mg/kgBB (216.2 pg/ml) and 200 mg/kgBB (118.7 pg/ml). Conclusions: This study concluded that methanol extract of songga wood has strong antioxidant activity and anti-inflammatory activity. The most effective dose to reduce IL-8 levels was 200 mg/kgBB, which was not significantly different from the positive control (p>0.05).